Conservative treatment of delayed cerebral radiation necrosis. Issue 12 (December 1984) - Shaw, P J; Bates, D
Abstract : A 63-year-old man developed delayed cerebral radiation necrosis following radiotherapy to a nasopharyngeal carcinoma. Complete resolution of his neurological deficit resulted from corticosteroid therapy alone. Serial CT scans showed the disappearance of the patients' mass lesion. The literature on cerebral necrosis following radiotherapy of extracranial neoplasms is reviewed with particular emphasis on management.